Prohibition of Marriage Due to Maqashid Sharia Perspective, An Approach - Saiin, Asrizal (Advances in Humanities and Contemporary Studies, 2021)
Every Muslim must adhere to or adhere to the Qur’an and Hadith. In Islamic law, it is known as maqashid sharia. Prohibition of carrying out a marriage because one-sucks can be seen from the maqashid sharia. in maqashid sharia, the purpose of Allah to make the law is to maintain the benefit of mankind, as well as to avoid mafsadat, both in this world and in the hereafter. The stipulation of the law is in the context of realizing human benefit. There are five main elements that are protected against the stipulation of the prohibition law to marry because they are in accordance with Islamic law. The five main elements are guarding religion (hifdz ad-Diin), guarding the soul (hifdz an-Nafs), maintaining reason (hifdz al-’Aql), guarding descent (hifdz an-Nasl), and protecting property (hifdz al-Mal).